2010
DOI: 10.1007/s10457-010-9320-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet inclusion of Tithonia diversifolia on feed intake, digestibility and nitrogen balance in tropical sheep

Abstract: Feed intake and digestibility were evaluated in sheep fed low quality Taiwan grass supplemented with Tithonia diversifolia. Four wether hair sheep were housed in metabolic cages and fed with either Control concentrate 20%, Tithonia 20, 35 or 50% in a Latin Square design. Adaptation and, feces and urine collection periods were 14 and 7 days, respectively. Feed intake was increased (P \ 0.01) from 58.5 in control to 86.1 g/kg 0.75 in sheep fed Tithonia. NDF intake and digestibility were affected by Tithonia leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
4
13
0
6
Order By: Relevance
“…diversifolia , has been used across experiments as a high quality forage that can replace concentrates in ruminants [1–3,13]. Past research has shown that T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diversifolia , has been used across experiments as a high quality forage that can replace concentrates in ruminants [1–3,13]. Past research has shown that T .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other tropical forages commonly used for milk production, T . diversifolia has greater protein and phosphorus content [1–3]. Additionally, some studies have shown that the nutritive value of T .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reports by [7]. [8] explaining that sampling should be done according to the collector"s interests, were also considered. Random sampling is recommended so complete sampling can be ensured.…”
Section: Diversity and Potential Use Of Weeds In Farm Production Systmentioning
confidence: 99%
“…A. Gray, also known as Mexican Sunflower, Botón de Oro, Wild Sunflower or Titonia, is a bush of the Asteraceae family, originating from Central America and widely distributed in tropical regions (Ramírez-Rivera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%